FENOMENA PUBLIKASI KONTEN DI MEDIA SOSIAL TIKTOK OLEH KONTEN KREATOR @URROFI_ - Sefina Putri Liana (2023)
Social media platforms adorn many virtual communities, each with unique characteristics. Seeing the various types of social media platforms that adorn the digital world, TikTok is one of the top choices for content creators in publishing works, especially for gen Z and some of gen Y. The development of TikTok is very rapid, so this momentum is utilized by creative individuals to play a role in creator content. This study aims to discover why the TikTok content creators behind the @urrofi_ account chose TikTok social media as a medium for publishing content. The research concept that will include in this research is content creator, social media, TikTok, content virality, and perceived ease of use with this type of qualitative research and Alfred Schutz's phenomenological approach. Data collection techniques through in-depth interviews and documentation. The object of this research is Daffa Urrofi's TikTok social media platform account, namely @urrofi_. There were 5 informants taken in this study. The data analysis techniques used in this study include the collection of life experience, horizontalization, significant statements, thematic analysis, and essence statements. Based on the research results, it was found that the reason for choosing TikTok as a publication medium by Daffa Urrofi was that he wanted to share knowledge or education about videography, a viral platform, reach a broad audience, ease of use of the application, and support from TikTok to develop content creators.